Ameliorative Effect of Neem Leaf and Pomegranate Peel Extracts in Coccidial Infections in New Zealand and V-Line Rabbits: Performance, Intestinal Health, Oocyst Shedding, Carcass Traits, and Effect on Economic Measures - Liza S. Mohammed; Eman A. Sallam; Sawsan S. El basuni; Amany S. Eldiarby; Mohamed Mohamed Soliman; Salama Mostafa Aboelenin; Seham F. Shehata (Animals, 2021)
Healthy, weaned, coccidial-free male rabbits from two breeds (New Zealand white (NZ) and V-line (VL)) were divided into 10 equal groups (5 groups each for NZ and VL) (3 replicates/group, 6 rabbits/replicate, 18 rabbits/group). All rabbits were inoculated with 5 × 104 Eimeria spp. oocysts (E. intestinalis (67%), E. magna (22%), and E. media (11%)) except for the rabbits in the first group (G1), which were inoculated with a sterile solution and served as a negative control. The remaining four groups were treated as follows: G2, no treatment/positive control, G3, treated with neem leaf extract, G4, treated with pomegranate peel extract (PPE), and G5, treated with a combination of neem leaf extract and PPE. For both breeds, our results showed that the use of neem leaf and/or pomegranate peel extract resulted in improved growth performance, with a significant improvement in relative feed conversion ratio (FCR) compared to the positive control groups, which recorded the worst values, as well as a significant (p ≤ 0.05) reduction in mean oocyst count compared to the positive control groups. We also observed downregulation of mRNA levels of IL-1βα, IL6, and TNF-α in the herbal treatment groups compared with the mRNA levels of these genes in the positive control groups. Herbal treatment with neem leaf and/or pomegranate peel extracts had positive effects on the NZ and VL rabbits experimentally infected with mixed Eimeria species, as evidenced by their healthy appearance, good appetite, no mortalities, an anticoccidial index > 120, and a significantly higher total return and net profit when compared to the positive control groups of both breeds. In NZ rabbits, the treatment with neem leaf extract alone (G3) or in combination with PPE (G5) recorded the most efficient economic anticoccidial activity.